The impact of glycated hemoglobin trajectories on hypertension risk: a retrospective cohort study - Sun, Yongbing; Shen, Yu; Liu, Ao; Zhao, Caiwen; Ji, Xiaoqi; Li, Xin; Zou, Zhi; Li, Zhonglin; Wu, Xiaoling; Wang, Yong; Liu, Min; Li, Yongli; et al. (Frontiers in Nutrition, 2025)
BackgroundGlycated hemoglobin (HbA1c) reliably reflects long-term glucose control and has been linked to hypertension development. This study investigates the relationship between baseline HbA1c levels, HbA1c trajectories, and hypertension risk.MethodsThis retrospective cohort study included 10,138 adults from health screenings at Henan Provincial People’s Hospital (January 2018–January 2025). Mean age was 54.03 ± 12.97 years, with 31.44% women and mean follow-up of 43.92 months. We analyzed hypertension incidence across HbA1c groups using Kaplan–Meier curves and identified HbA1c trajectory patterns using latent class trajectory modeling (LCTM). Cox proportional hazards models evaluated associations between baseline HbA1c tertiles, HbA1c trajectories, and hypertension risk. Restricted cubic splines explored dose–response relationships.ResultsDuring follow-up, 3,452 participants (34.05%) developed hypertension. After adjustment, participants in the highest baseline HbA1c tertile had significantly increased hypertension risk versus the lowest tertile (HR = 1.49, 95%CI: 1.31–1.70). LCTM identified three distinct trajectories: low-stable (5.57 ± 0.36%), medium-stable (6.45 ± 0.59%), and high-stable (8.42 ± 1.39%). Compared to low-stable trajectory, medium-stable and high-stable groups showed significantly increased risks (HR = 1.38, 95%CI: 1.24–1.53; HR = 2.71, 95%CI: 2.21–3.32, respectively). Restricted cubic spline analysis revealed a J-shaped relationship with an inflection point at HbA1c = 5.70% (P for nonlinearity < 0.001).ConclusionElevated baseline HbA1c levels, particularly above 5.70%, and medium-to-high stable HbA1c trajectories significantly increase hypertension risk among adults undergoing health screening. HbA1c could serve as a valuable biomarker for hypertension risk assessment.